2013
DOI: 10.1371/journal.pone.0058711
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Success in Cancer: Industry Compared to Publicly Sponsored Randomized Controlled Trials

Abstract: ObjectiveTo assess if commercially sponsored trials are associated with higher success rates than publicly-sponsored trials.Study Design and SettingsWe undertook a systematic review of all consecutive, published and unpublished phase III cancer randomized controlled trials (RCTs) conducted by GlaxoSmithKline (GSK) and the NCIC Clinical Trials Group (CTG). We included all phase III cancer RCTs assessing treatment superiority from 1980 to 2010. Three metrics were assessed to determine treatment successes: (1) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…15,36 These relationships are likely relevant in studies with industry collaboration as well as in those that are not industry funded, which may blunt the impact of collaboration itself. However, simple industry funding has been associated with positive results in oncology trials, 18 with a similar effect size as in the literature overall, 5 so a fundamental difference between oncology and other areas is unlikely.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…15,36 These relationships are likely relevant in studies with industry collaboration as well as in those that are not industry funded, which may blunt the impact of collaboration itself. However, simple industry funding has been associated with positive results in oncology trials, 18 with a similar effect size as in the literature overall, 5 so a fundamental difference between oncology and other areas is unlikely.…”
Section: Discussionmentioning
confidence: 87%
“…First, it may reflect a general evolution over time with the impact of industry involvement on study results waning in recent years. 18 Most prior studies of the association between funder and outcome reflected older publications 3,4,27 and the single study demonstrating higher rates of positive results among trials with industry collaboration included trials published in 2011– 2012, whereas our study included trials published between 2013 and 2015. A possible shift in recent years may be related to a number of interventions to increase transparency and reduce bias.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Low publication rates have been found for randomized clinical trials in many fields, [913] and specifically in industry-sponsored trials [9, 10, 12]. Industry-sponsored trials that did get published have been shown to more often find a treatment effect in benefit of the sponsor’s treatment [14, 15]. Additionally, examples exist of intentional withholding of trial reports from publication due to results not in favor of the sponsor’s drug [16].…”
Section: Discussionmentioning
confidence: 99%